THE SOCIO-ECONOMIC FORMATION MECHANISM OF CLUSTER SYSTEMS AND ITS ROLE IN SUSTAINABLE ECONOMIC DEVELOPMENT - Karimova Nilufar Sadriddin kizi (International Journal of Literature and Language Studies, 2026)
This article examines the socio-economic formation mechanism of cluster systems and their role in ensuring sustainable economic development in modern economies. The study analyzes the theoretical foundations of cluster development, the institutional and organizational factors influencing cluster formation, and the economic mechanisms that enhance regional competitiveness, investment attractiveness, and innovation activity. Particular attention is given to the interaction between enterprises, government institutions, financial structures, and scientific-educational organizations within cluster systems. The article also evaluates the socio-economic effects of clusters, including employment growth, efficient resource utilization, technological modernization, and the improvement of production efficiency. Based on international experience and the ongoing economic reforms in Uzbekistan, the research highlights the importance of cluster systems in accelerating industrial diversification, strengthening territorial economic integration, and increasing export potential. The findings demonstrate that the effective formation of cluster systems contributes significantly to macroeconomic stability, regional development, and long-term socio-economic sustainability.